Effects of cultural intelligence, government policies and host country national characteristics on international student adjustment and performance - Luke, Balami Emmanuel (2017)
International student cross-cultural adjustment at the host country has attracted researchers’ attention over the years, especially with the phenomenal proliferation and internationalisation of higher education in response to globalisation. The international student encounters problems of cross-cultural adjustment at the country of choice due to unfamiliar cultural environment. The international student’s crosscultural adjustment has close relationship to student performance at the destination of choice in the literature (Taufiki & Dawi, 2014; Wan, et al., 2013). This study explores the predictive relevance of the following driver constructs: Cultural Intelligence (CQ), Host Country National Characteristics (HCNc) Government Policies (GP) on the following dependent variables-Cross-Cultural Adjustment (CCA) and Student Performance (SP). This is based on Ang, et al’s., (2007) recommendations to test the robustness of the predictive capabilities of Cultural Intelligence on Cross-Cultural Adjustment in terms of individual difference, ethnocentrism, geographical scope and social identity. Equally, the mediating effect of Cross-Cultural Adjustment on Student Performance was tested and the moderating effect of Host Country National Characteristics on Cross-Cultural Adjustment and Student Performance tested. The outcome serve as bases for recommendations to policy makers and future researchers of the significance of these constructs to international student retention effort by host countries. Because of the complex nature of this study model, the matching robustness of the Partial Least Square-Structural Equation Modelling software (PLS-SEM) makes it to be the most appropriate software for analysing the data set for this study. The survey approach employed to collect data from 214 international students from two Malaysian public universities using a multi-method approach. The beta coefficient, coefficient of determination and predictive relevance of the driver constructs were analysed for Cross-Cultural Adjustment and Student Performance, the results indicates statistical significance. Then, the effect size (f2 & q2) of the driver constructs were also tested with small effect sizes. All the hypothesised relationships were supported at 95% confidence interval with corresponding t-values above the 1.96 threshold value. This was followed by the test of the total effect of the driver constructs on the ultimate dependent variable-Student Performance, the result indicated that Government Policies has the highest total effect on the student performance construct, this was followed by Cultural Intelligence and lastly by the Host Country National Characteristic construct. However, the hypothesised model mediation and moderation tests failed, but after a systematic post hoc procedure the Cultural Intelligence construct was expunge a competing model emerged. This new model was used in testing mediation, the Cross-Cultural Adjustment construct now fully mediated the Host Country National Characteristic—Student Performance relationship, however; Government Policies—Student Performance relationship was not mediated. The moderating effect of Host Country National Characteristics construct on the Government Policies—Student Performance relationship was supported, but did not moderate the Cross-Cultural Adjustment—Student Performance and the Government Policies- Cross-Cultural Adjustment relationships. In summary, the analysis results so far proved that Government Policies is the most significant in predicting Student Performance, the Cross-Cultural Adjustment construct is a full mediator to the Host Country National Characteristic—Student Performance relationship, and finally, Host Country National moderates the relationship between Government Policies and Student Performance relationship. Suggestions to policy makers and recommendations to future researchers are in the implications to practice and recommendations sections of this thesis (Section 7.6).